Dysregulated cytokine expression by CD4+ T cells from post-septic mice modulates both Th1 and Th2-mediated granulomatous lung inflammation. - William F Carson; Toshihiro Ito; Matthew Schaller; Karen A Cavassani; Stephen W Chensue; Steven L Kunkel (PLoS ONE)
Previous epidemiological studies in humans and experimental studies in animals indicate that survivors of severe sepsis exhibit deficiencies in the activation and effector function of immune cells. In particular, CD4+ T lymphocytes can exhibit reduced proliferative capacity and improper cytokine responses following sepsis. To further investigate the cell-intrinsic defects of CD4+ T cells following sepsis, splenic CD4+ T cells from sham surgery and post-septic mice were transferred into lymphopenic mice. These recipient mice were then subjected to both TH1-(purified protein derivative) and TH2-(Schistosoma mansoni egg antigen) driven models of granulomatous lung inflammation. Post-septic CD4+ T cells mediated smaller TH1 and larger TH2 lung granulomas as compared to mice receiving CD4+ T cells from sham surgery donors. However, cytokine production by lymph node cells in antigen restimulation assays indicated increased pan-specific cytokine expression by post-septic CD4+ T cell recipient mice in both TH1 and TH2 granuloma models. These include increased production of T(H)2 cytokines in TH1 inflammation, and increased production of T(H)1 cytokines in TH2 inflammation. These results suggest that cell-intrinsic defects in CD4+ T cell effector function can have deleterious effects on inflammatory processes post-sepsis, due to a defect in the proper regulation of TH-specific cytokine expression.